Measurement and modelling of flow and turbulence above a biomass boiler continuous ash discharge stoker grate - Du Plessis, Hennie (Stellenbosch : Stellenbosch University, 2025)
Du Plessis, J. 2025. Measurement and modelling of flow and turbulence above a biomass boiler continuous ash discharge stoker grate. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/ee223a58-b395-4ae1-a641-92d79017ab30